Influence of common simplifications on the drying of cement-based materials up to moderate temperatures. (April 2020) - Cheikh Sleiman, Hani; Briffaut, Matthieu; Dal Pont, Stefano; Tengattini, Alessandro; Huet, Bruno
Highlights: Drying response error map for monophase compared to multiphase model is obtained. The effect of desorption isoterm thermal evolution on drying response is quantified. The effect of intrinsic permeability thermal evolution on drying kinetics is quantified. Abstract: The drying of cement-based materials affects directly their durability, which has a major financial/societal impact. Notably, the variation of saturation of the porous network as well as drying shrinkage are fundamental processes since they drive together cracking and the penetration rate of aggressive chemicals. Many macroscopic models describe the moisture transport within porous media. They can be broadly divided into two main categories: multiphase macro-models which take into account the presence of three fluid phases (liquid water, vapor and dry air), and simplified models considering less phases under the main assumption of constant gas pressure during the drying process. Moreover, the choice of different behavior laws, which describe different evolutions of desorption isotherms, relative permeability, permeability to liquid water in function of temperature, has a major impact on mass loss amount and kinetics. Quantification of these simplifications effects regarding the used model and the choice of behavior laws was done by comparing mass loss response surfaces in a relative humidity and temperature space for multiple configurations. The results show relative error maps at early, mid and late drying stages for every compared case.